Reliability and Validity of Composite Scores from the NIH Toolbox Cognition Battery in Adults. (24th June 2014) - Heaton, Robert K.; Akshoomoff, Natacha; Tulsky, David; Mungas, Dan; Weintraub, Sandra; Dikmen, Sureyya; Beaumont, Jennifer; Casaletto, Kaitlin B.; Conway, Kevin; Slotkin, Jerry; Gershon, Richard
Abstract: This study describes psychometric properties of the NIH Toolbox Cognition Battery (NIHTB-CB) Composite Scores in an adult sample. The NIHTB-CB was designed for use in epidemiologic studies and clinical trials for ages 3 to 85. A total of 268 self-described healthy adults were recruited at four university-based sites, using stratified sampling guidelines to target demographic variability for age (20–85 years), gender, education, and ethnicity. The NIHTB-CB contains seven computer-based instruments assessing five cognitive sub-domains: Language, Executive Function, Episodic Memory, Processing Speed, and Working Memory. Participants completed the NIHTB-CB, corresponding gold standard validation measures selected to tap the same cognitive abilities, and sociodemographic questionnaires. Three Composite Scores were derived for both the NIHTB-CB and gold standard batteries: "Crystallized Cognition Composite, " "Fluid Cognition Composite, " and "Total Cognition Composite" scores. NIHTB Composite Scores showed acceptable internal consistency (Cronbach's alphas=0.84 Crystallized, 0.83 Fluid, 0.77 Total), excellent test–retest reliability (r: 0.86–0.92), strong convergent (r: 0.78–0.90) and discriminant (r: 0.19–0.39) validities versus gold standard composites, and expected age effects ( r =0.18 crystallized, r =−0.68 fluid, r =−0.26 total). Significant relationships with self-reported prior school difficulties and current health status, employment, and presence of a disability provided evidence of external validity. The NIH Toolbox Cognition Battery Composite Scores have excellent reliability and validity, suggesting they can be used effectively in epidemiologic and clinical studies. ( JINS, 2014, 20, 1–11)